Short-term dentoalveolar effects of aesthetic lip bumper appliance: A longitudinal cases-series and pilot study - M. Palone; F. Averta; G. Poma; F. Cremonini; ML. Degl'Innocenti; L. Lombardo (Saudi Dental Journal)
Background: To investigate the short-term dentoalveolar effects on the mandibular arch of a modified, aesthetic lip bumper (ALBAa). The study sample comprised 23 patients (13 boys and 10 girls, with a mean age of 9.5 ± 1.8 years) in mixed dentition, with no previous orthodontic treatment. For each patient, a scan of the mandibular arch was digitally acquired pre-treatment (T0), and at 3 months (T1), 6 months (T2) and 9 months (T3) post-treatment. Linear intra-arch measurements, Little’s irregularity index of the amount of mandibular anterior crowding, and the crown tipping values on all mandibular teeth were measured and compared statistically between time points. ANOVA and subsequent post-hoc tests were performed, considering a p-value of < 0.05 as significant. Results: Linear intra-arch distances and crown tipping values on the mandibular teeth increased between the following time points: T0vsT1, T1vsT2, T0vsT2 and T0vsT3 (p < 0.05), although in the last three months of observation (T2vsT3) they only reached statistical significance at the lower incisors and lower left premolar concerning crown tipping values. There was a statistically significant decrease in anterior crowding throughout the observational period (p < 0.05), and this effect was equally distributed across the different time points investigated. Conclusions: ALBAa therapy led to an increase in both linear intra-arch distances and crown tipping values, with a reduction in Little's index. The distribution of the effects reported across the observational period depended on the mechanism of action (mechanical vs. functional).